2020
DOI: 10.1039/c9en01435g
|View full text |Cite
|
Sign up to set email alerts
|

Preferential phosphate sorption and Al substitution on goethite

Abstract: The Al-substitution affected not only the basal spacing between adjacent lattice planes but also the structural arrangement in goethite which results in the Al-preferential PO4 sorption on Al-substituted goethite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The linearity observed in both theoretical and optimized site densities with respect to Al content points toward the direction of enhanced distribution of Al at the ferrihydrite surface compared to the bulk composition. A similar conclusion was reached by Hsu et al for Al substitution in goethite based on Fe-XAS and XPS analyses.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The linearity observed in both theoretical and optimized site densities with respect to Al content points toward the direction of enhanced distribution of Al at the ferrihydrite surface compared to the bulk composition. A similar conclusion was reached by Hsu et al for Al substitution in goethite based on Fe-XAS and XPS analyses.…”
Section: Resultssupporting
confidence: 85%
“…There is currently no experimental evidence to support that Al necessarily substitutes Fe on the surface in a similar pattern as in the bulk structure of ferrihydrite. Recently, Hsu et al 35 showed Al segregation near the surface of Algoethites utilizing iron K-edge X-ray absorption (Fe-XAS) and X-ray photoelectron spectroscopy (XPS). Adams et al 33 modeled ζ-potential titrations with the 15-site model assuming a uniform distribution between the bulk and surface structure.…”
Section: Al-ferrihydrite Surface Structure and Surface Complexation M...mentioning
confidence: 99%
See 2 more Smart Citations
“…Ni et al found Al-substituted goethite presented with an increase in adsorption capacity of Cr(VI) compared with pristine goethite [55]. Hsu et al showed the maximum adsorption capacity of phosphate rose from 135 to 584 mmol/kg when Al/(Al + Fe) mol% changed from 0 to 17.4% [56]. Tufo et al suggested that a small incorporation of Al would enhance the adsorption properties of the goethite surface.…”
Section: Introductionmentioning
confidence: 99%